New Lessons from Australia to Improve Pension Outcomes - Price, William (World Bank, Washington, DC, 2016)
The Australian Government commissioned the independent Financial System Inquiry or ‘Murray Review’ to provide recommendations to improve private pensions (superannuation), as well as financial system resilience, innovation and consumer protection. This continues Australia’s proactive approach - regularly reviewing how to improve a system that already has good features. The recommendation for a clear (and legally binding) statement of what the retirement system is trying to achieve is a sensible move. It mirrors what is happening in a range of World Bank projects, to start with the long-run outcomes and then work backwards to find the best ways to achieve them, in terms of regulation, supervision, market structure and efficient infrastructure. This note reviews the key analysis and recommendations from the review of the private pension system in Australia known as the ‘Murray Review’. It provides a commentary on the implications for pension reforms using World Bank experience in a range of projects.